John Moores Liverpool Exhibition nr. 19. - Walker Art Gallery, Liverpool; Foster, Richard; Treuherz, Julian (Liverpool : Walker Art Gallery Liverpool, 1995)
Leapman, David ; Darach, Peter ; Gibbons, Jeff ; Green, Paul ; Harris, Jane ; Hyslop, Joanna ; Jones, Lucy ; Kondracki, Henry ; Mabbutt, Mary ; Rielly, James ; Walker, Jane ; Abrahams, Peter ; Ainsworth, Mark ; Allen, Joe ; Appleby, Christopher ; Baraitser, Alexandra ; Bell, Trevor ; Betts, Simon ; Brook, James ; Butler, Paul ; Chell, Edward ; Dalwood, Dexter ; Stefano, Arturo Di ; Evans, Geraint ; Fisher, Chris ; Forster, Noel ; Fournier, Christian ; Francis, Mark ; Gildea, Paul ; Gopal-Chowdhury, Paul ; Green, Anthony ; Greenland, Martin ; Guinness, Harriet ; Holden, John ; Irvin, Albert ; Jones, Huw ; Jones, Trevor ; Jones, Wynn ; Kiff, Ken ; Lannoy, Richard ; Lochore, Brad ; Martin, David G. ; McComb, Leonard ; Nathan, Janet ; Nicholls, Iain ; Nuttall, Richard ; O'Donoghue, Hughie ; Ofili, Chris ; Osuga, Jiro ; Pliarides, Vangelis ; Press, Frances ; Rimmer, John ; Robson, Gavin ; Shepherd, Richard ; Stahl, Andrew ; Wallinger, Mark ; Warnock, Rose ; Wedge, Martin ; Yates, Tom ; Zia, Partou
biografie
John Moores Liverpool Exhibition nr. 19, Walker Art Gallery Liverpool, 20 October 1995 to 28 January 1996
Engels
boek